LEARNERS’ PERSPECTIVES ON THE APPLICATION OF ROLE-PLAYING ACTIVITIES IN LEGAL ENGLISH CLASSES - Nhạc, Hương Thanh (IJIET (International Journal of Indonesian Education and Teaching), 2025)
Role-play, an integrated language teaching method, is highly recommended in English-for-specific-purposes classes for its valuable benefits. This paper focuses on investigating learners’ perspectives on role-play activity utilization in legal English lessons at Hanoi Law University. To achieve the aim, a 15-week study was carried out with the participation of sixty-seven second-year law students who were instructed with role-playing activities in legal English lessons. Data were collected through survey questionnaires and in-depth semi-structured interviews, which addressed the benefits of role-play in terms of enhancing learners’ legal English skills and legal English terms, as well as fostering their learning motivation. Accordingly, instructors might consider such findings to maximize the efficacy of role-playing activities in teaching legal English.